Mushrooms as health foods - Mori, Kisaku (Japan publications, 1974)
This role of fungi in the production of such wholesome foods as yeast, yogurt, and cheese has long been recognizes and appreciated. The body requires the kind of substances the fungi provide, and the richest source of them is mushrooms, wich are fungi in forms the human body can readily use.